PENYELESAIAN SENGKETA KEBIJAKAN PRODUK KEMASAN POLOS PRODUK ROKOK AUSTRALIA DALAM WTO [Resolution of the Dispute over Australia's Rules and Policies for the Plain Packaging of Cigarette Products in the WTO] - Jantarda Mauli Hutagalung; Clara Ignatia Tobing (Law Review, 2020)
AbstractThe sovereignty of a country to issue a policy or regulation in the field of international trade is limited by the enactment of the provisions in the World Trade Organization (WTO), especially for countries that have ratified the GATT / WTO. If a country issues rules and/or policy that conflict with WTO provisions, it will result in the country being sued by another country. As happened with the policy issued by Australia. Indonesia is suing Australia to the WTO for the rules and/or policies for the plain packaging of cigarette products (The Tobacco Plain Packaging Act 2011) imposed by Australia. The policy is considered contrary to the provisions of the WTO, specifically the provisions of TRIPS (Trade Related Aspects of Intellectual Property Rights). This research utilizes a normative juridical method by paying attention to legal materials such as legal principles, legal principles, international conventions, and legislation relating to the problem of The Tobacco Plain Packaging Act. From the results of the study can be seen WTO considerations in this case. In addition, there are also advantages and disadvantages of the implementation of The Tobacco Plain Packaging Act in the future.Keywords: WTO/GATT, The Tobacco Plain Packaging Act, International Economic Law AbstrakKedaulatan suatu negara untuk mengeluarkan suatu kebijakan atau peraturan dalam bidang perdagangan internasional dibatasi oleh berlakunya ketentuan-ketentuan dalam World Trade Organization (WTO), terutama bagi negara-negara yang telah meratifikasi GATT/WTO. Apabila negara mengeluarkan aturan dan/atau kebijakan yang bertentangan dengan ketentuan WTO akan  mengakibatkan negara tersebut digugat oleh negara lain. Seperti yang terjadi dengan kebijakan yang dikeluarkan oleh Australia. Indonesia menggugat Australia ke WTO atas aturan dan/atau kebijakan kemasan polos produk rokok (The Tobacco Plain Packaging Act 2011) yang diberlakukan oleh Australia. Kebijakan tersebut dianggap bertentangan dengan ketentuan WTO, khususnya ketentuan TRIPS (Trade Related Aspect of Intellectual Property Rights). Penelitian ini menggunakan metode yuridis normatif dengan memperhatikan bahan hukum seperti asas-asas hukum, prinsip-prinsip hukum, konvensi internasional, serta perundang-undangan yang berkaitan dengan masalah The Tobacco Plain Packaging Act. Dari hasil penelitian dapat terlihat pertimbangan WTO dalam kasus ini. Selain itu, terlihat juga keuntungan dan kekurangan dari pemberlakuan The Tobacco Plain Packaging Act ke depannya.Kata kunci: WTO/GATT, The Tobacco Plain Packaging Act, Hukum Ekonomi Internasional